E4orf1, an Adeno-viral protein, attenuates renal lipid accumulation in high fat fed mice: A novel approach to reduce a key risk factor for chronic kidney disease - Afruza, Rownock (Heliyon, 2020)
Obesity and hyperlipidemia are independent risk factors of chronic kidney disease (CKD). In mice, diet induced obesity accelerates lipogenesis, lipid accumulation, and injury in kidneys. Expression of adenoviral protein, E4orf1, improves glucose clearance and reduces endogenous insulin secretion to glucose challenge in mice. Therefore, in this pilot study, we examined, if enhanced glycemic control in HFD fed E4orf1 transgenic (E4orf1-Tg) mice, will reduce renal lipogenesis and lipid accumulation. In two separate experiments, E4orf1-Tg mice were fed 60% (kcal) high-fat diet (HFD) supplemented with doxycycline for 10-weeks or 20-weeks along with wild-type (C57BL6/J) or E4orf1-non-transgenic (E4orf1-non-Tg) control mice, respectively. Protein expression of Fatty Acid Synthase (FAS) and Acetyl-CoA Carboxylase (ACC), accumulation of triglyceride (TG) along with mRNA levels of lipid metabolism and injury markers were determined in kidneys. Renal expression of FAS and ACC, and TG content was significantly reduced in E4orf1-Tg mice compared to controls. E4orf1-Tg mice show significant increase in genes involved in mitochondrial fatty acid oxidation and oxidative stress compared to wild-type mice after 10-weeks of HFD. However, mice exposed to 20-weeks of HFD, show no difference in gene expression. E4orf1 expression reduces lipid synthesis and accumulation in kidneys despite HFD, which may be due to attenuation of hyperinsulinemia by E4orf1.